Massive transfusion in the pediatric population: A systematic review and summary of best-evidence practice strategies. Issue 4 (April 2019) - Kamyszek, Reed W.; Leraas, Harold J.; Reed, Christopher; Ray, Candice M.; Nag, Uttara P.; Poisson, Jessica L.; Tracy, Elisabeth T.
Abstract : BACKGROUND: Pediatric patients require massive transfusion (MT) in a variety of settings. Multiple studies of adult MT support balanced ratio transfusion to improve outcomes; however, it is unclear if these findings can be extrapolated to pediatric populations. The use of balanced transfusion ratios, MT protocols, hemostatic adjuncts, and even the definition of a MT in children are all open questions. This review presents details of care from current practices in pediatric MT and summarizes practice strategies while providing insight from our single-center experience. METHODS: PubMed, EMBASE, and Web of Science were searched using MeSH index and free-text terms for articles from 1946 to 2017. Articles were independently reviewed by two reviewers. Studies were assessed for definition of MT, factors predicting MT, MT complications, blood product ratios, hemostatic adjuncts, protocol logistics, and clinical outcomes. RESULTS: A heterogeneous composite of 29 articles was included in the analysis. Of these, 45% reported a formal transfusion protocol or adopted one during the study. Seven unique definitions of pediatric MT were reported; the most common was >1 total blood volume within 24 hours. A total of 18, 369 patients were assessed, and 1, 163 received MT (6.3%). Overall mortality for patients requiring MT in studies reporting mortality was high (range 14.7% to 51.2%). We identified 14 patients receiving MT at our center with an age range of 8 months to 18 years and average transfusion of 38.1 mL/kg red blood cells (range: 22.1 mL/kg to 156.7 mL/kg). CONCLUSIONS: Current practices of pediatric MT demonstrate a variety of site-specific interventions with a persistently high mortality rate. A national focus on improving techniques of MT in children has the potential to save the lives of these children. LEVEL OF EVIDENCE: Systematic review, levels IV and V.